2022
DOI: 10.1155/2022/6091834
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Toxoplasma Effects of Dracocephalum Polychaetum Essential Oil

Abstract: Background. Toxoplasma gondii is a common parasitic disease with a cosmopolitan prevalence, causing severe health problems. Although chemotherapy for toxoplasmosis is readily available, most have side effects. Objectives. This study assesses the Dracocephalum polychaetum essential oil against T. gondii activity. In vitro, the anti-Toxoplasma effects of D. polychaetum essential oils with different concentrations were evaluated. Methods. In the present study, T. gondii RH strain tachyzoites were exposed to D. po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Chinese medicine from natural plants is widely used to control different parasites due to their safety and effectiveness. In recent years, many researchers focused on screening anti-Toxoplasma drugs from natural plant extracts, such as plant essential oils and other products [35,36]. Numerous studies…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese medicine from natural plants is widely used to control different parasites due to their safety and effectiveness. In recent years, many researchers focused on screening anti-Toxoplasma drugs from natural plant extracts, such as plant essential oils and other products [35,36]. Numerous studies…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medicine from natural plants is widely used to control different parasites due to their safety and effectiveness. In recent years, many researchers focused on screening anti-Toxoplasma drugs from natural plant extracts, such as plant essential oils and other products [35,36]. Numerous studies have shown that artemisinin and its derivatives not only effectively treat malaria, but also inhibit the proliferation of cancer cells and promote their apoptosis and ferroptosis [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…These natural products have been proved to be an alternative for chemical agents in the pharmaceutical industry (Molaei et al., 2021 ; Petrovska, 2012 ; Sofowora et al., 2013 ). Recently, natural extracts of plants have been considered as anti‐ Toxoplasma components (Choi et al., 2013 ; Kavitha et al., 2012 ; Khamesipour et al., 2022 ; Mohammad Rahimi et al., 2020 ; Nemati et al., 2022 ). Rosa rubiginosa ( Rosa eglanteria L.), known as rose hips ( Rosa spp., Rosaceae ), are wild rose bushes with more than 100 species, which are widely used in the preparation of cosmetic products and the food industry (Franco, Pinelo, et al., 2007 ; Loetscher et al., 2013 ; Santana et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Dracocephalum belongs to the Labiatae family and consists of about 60 annual or perennial herbs that are greatly expanded in the North hemisphere, Southern Europe, North America, North Africa, and temperate Asia (Heydari et al, 2019;Uchiyama et al, 2004). It has been described as the presence of Dracocephalum essential oil as a major constituent with good pharmacological properties (Khamesipour et al, 2022;Mahmood et al, 2005). In addition, numerous studies showed that these oils present important effects acting as antioxidants (Ehsani et al, 2017;Fallah et al, 2018;Sonboli et al, 2012;Zhang et al, 2008), insecticidal (Chu et al, 2011;Özek et al, 2016), phytotoxic (Jalaei et al, 2015;Suleimen et al, 2017), cytotoxic (Sonboli et al, 2012), antinociceptive (Golshani et al, 2004), antispasmodic (Sadraei et al, 2015), antimicrobial (Ehsani et al, 2017;Lee et al, 2007) and antiparasitic (Ghanadian et al, 2021;Khamesipour et al, 2020;Nekoei et al, 2022).…”
Section: Introductionmentioning
confidence: 99%